Advancing the science and practice of ecological nutrient management for smallholder farmers - Drinkwater, Laurie E.; Snapp, Sieglinde S. (Frontiers in Sustainable Food Systems, 2022)
Soil degradation is widespread in smallholder agrarian communities across the globe where limited resource farmers struggle to overcome poverty and malnutrition. This review lays out the scientific basis and practical management options for an ecologically based approach to sustainably managing soil fertility, with particular attention to smallholder subsistence systems. We seek to change the trajectory of development programs that continue to promote inorganic fertilizers and other high input strategies to resource constrained smallholders, despite ample evidence that this approach is falling short of food security goals and contributing to resource degradation. Ecological nutrient management (ENM) is an agroecological approach to managing the biogeochemical cycles that govern soil ecosystem services and soil fertility. The portfolio of ENM strategies extends beyond reliance on inorganic fertilizers and is guided by the following five principles: 1) Build soil organic matter and other nutrient reserves. 2) Minimize the size of N and P pools that are the most susceptible to loss. 3) Maximize agroecosystem capacity to use soluble, inorganic N and P. 4) Use functional and phylogenetic biodiversity to minimize bare fallows and maximize presence of growing plants. 5) Construct agroecosystem and field scale mass balances to track net nutrient flows over multiple growing seasons. Strategic increases in spatial and temporal plant species diversity is a core ENM tactic that expands agroecosystem multifunctionality to meet smallholder priorities beyond soil restoration and crop yields. Examples of ENM practices include the use of functionally designed polycultures, diversified rotations, reduced fallow periods, increased reliance on legumes, integrated crop-livestock production, and use of variety of soil amendments. These practices foster soil organic matter accrual and restoration of soil function, both of which underpin agroecosystem resilience. When ENM is first implemented, short-term yield outcomes are variable; however, over the long-term, management systems that employ ENM can increase yields, yield stability, profitability and food security. ENM rests on a solid foundation of ecosystem and biogeochemical science, and despite the many barriers imposed by current agricultural policies, successful ENM systems are being promoted by some development actors and used by smallholder farmers, with promising results.